2023
DOI: 10.1155/2023/5878402
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Deep Hyperthermia Combined with Intraperitoneal Chemotherapy on Liver-Kidney Function, Immune Function, and Long-Term Survival in Patients with Abdominal Metastases

Abstract: Objectives. To analyze the effects of deep hyperthermia combined with intraperitoneal chemotherapy on liver-kidney function, immune function, and long-term survival in patients with abdominal metastases. Methods. A total of 88 patients with abdominal metastases confirmed in the hospital were enrolled as the research objects between August 2018 and August 2021. They were randomly divided into control group (n = 44) and observation group (n = 44). The control group was treated with intraperitoneal chemotherapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%